Feminizam i religija u 21. stoljeću – Tehnologija, dijalog i širenje granica / Feminism and Religion in the 21st Century – Technology, Dialogue, and Expanding Borders - Kurić, Đermana (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
This text is a review of a book Feminism and Religion in the 21st Century, translated by MSc Aida Spahić, TPO Fondation Sarajevo, 2022.